Reduction in faecal excretion of Salmonella typhimurium strain F98 in chickens vaccinated with live and killed S. typhimurium organisms - Barrow, P. A.; Hassan, J. O.; Berchieri, A. [UNESP] (Cambridge University Press (CUP), 1990)
Chickens given orally at 4 days of age a smooth spectinomycin resistant mutant (Spcr) of Salmonella typhimurium strain F98 excreted the organism in their faeces for approximately 4 weeks. Following oral administration of a nalidixic acid resistant (Nalr) mutant of the same strain 4 weeks later when later when the chickens had virtually cleared themselves of the first infection, these chickens excreted far fewer salmonella organisms and for a shorter time than did a previously uninfected control group of chickens which were infected at the same time with the Nalr mutant. Chickens inoculated intramuscularly at 4 days developed a similar immunity to challenge and also excreted the immunizing strain in their faeces. In contrast intramuscular inoculation or incorporation into the food of formalin-killed S. typhimurium organisms had little lasting effect on the faecal excretion of the challenge strain. Two attenuated mutants of strain F98 Nalr were produced: one was a rough strain produced by lytic bacteriophage and the other was an aro A auxotrophic mutant which had been cured of the 85 kilobase–pair virulence–associated plasmid. These mutants were avirulent for chickens, mice, calves and man and when ingested by human volunteers did not persist in the faeces. When inoculated intramuscularly into chickens they produced an early reduction in faecal excretion of the challenge strain (Spcr) which was not maintained. Oral administration of both strains produced reductions in faecal excretion of the challenge strain. This was much more noticeable with the rough strain which was itself excreted for a much longer period than the parent strain. © 1990, Cambridge University Press. All rights reserved.